Comparison and Design of Multi-Storied Buildings in All Four Zones, By Using STAAD Pro, A Review - Pushkar Lal Sahu; Bhojram Sahu (International Journal of Scientific Research in Civil Engineering, 2025)
In civil engineering structure seismic design of multi-storey building requires both static and dynamic analysis are perform. Static analysis is performed for regular buildings upto 90m height in zone II & III. Dynamic analysis is performed for both regular and irregular buildings in zone IV & V. Dynamic analysis is eighter performed by the “Time History Method” or “Response Spectrum Method”. The weakness arises due to discontinuity in mass, stiffness and geometry of structure. Mass irregularity shall be considered to exist where the weight of any storey is more than 200% of that of its adjacent storeys. There is necessary to construct a structure which is earthquake resistance at a particular level of intensity of shaking a structure.